Ali's pretty little lies : a Pretty little liars prequel novel - Shepard, Sara, 1977- (Pretty little liars, 2013)
It's the end of seventh grade, and Alison DiLaurentis and her friends are the girls of Rosewood Day. Ali runs her clique with an iron fist, and she's got enough dirt on Hanna, Emily, Aria, and Spencer to keep them in line. But Ali's hiding a dark secret of her own, something so huge it would destroy everything if it ever got out... and in Rosewood, deadly secrets have deadly consequences...